2020
DOI: 10.21203/rs.3.rs-42898/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High prevalence of SARS-CoV-2 infection among symptomatic healthcare workers in a large university tertiary hospital in São Paulo, Brazil

Abstract: Background: Brazil became the epicenter of the COVID-19 pandemic in Latin America since May 2020, reporting the highest number of cases and deaths in the region. Healthcare workers (HCWs) are at increased risk of SARS-CoV-2 infection, experiencing a significant burden from COVID-19. Identifying and understanding the clinical characteristics and risk factors associated with infection are of paramount importance to inform screening strategies and infection control practices in this scenario. The aims of this stu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…These results are in agreement with another study that shows no correlation between them (11). However, some studies reported that general practitioners have higher mortality among doctors (7,13) because they spend prolonged periods of time with COVID-19 patients, have more shift timing, and get more exposure to higher distress, which put them in the high-risk group (13).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are in agreement with another study that shows no correlation between them (11). However, some studies reported that general practitioners have higher mortality among doctors (7,13) because they spend prolonged periods of time with COVID-19 patients, have more shift timing, and get more exposure to higher distress, which put them in the high-risk group (13).…”
Section: Discussionsupporting
confidence: 91%
“…In terms of gender, the mortality in infected females and males was 1.3% and 7.4%, which is a statistically signi cant difference like that found in other studies (7,11,13).…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…A number of other publications found similar associations between symptoms and SARS-CoV-2 testing for symptomatic HCP. [7][8][9][10][11] Most demonstrated the presence of fever, cough, ageusia, or anosmia are associated with a higher odds of testing positive; few have similarly shown gastrointestinal symptoms and pharyngitis may be associated with significantly lower odds. However, prior results have been hampered by: (1) limited Symptoms included cough, chills, fever, anosmia, ageusia, headache, and myalgia.…”
Section: Discussionmentioning
confidence: 99%
“…Data on prevalence of, and risk factors for, COVID-19 in HCP exist [2][3][4][5][6] ; however, there is little information on the relationship between (1) health care role, (2) contact history, and (3) symptoms with subsequent SARS-CoV-2 polymerase chain reaction (PCR) testing results for symptomatic HCP. [7][8][9][10][11] We performed a prospective cohort study of symptomatic HCP at a large, tertiary care center to determine these associations.…”
mentioning
confidence: 99%